How can fng grow faster via entering and thriving in the online advertising market?: pricing strategy - Moreira, Carolina Pires Soares Do Nascimento (2020)
The current advertising landscape in Portugal reveals that the Pay- TV market has reached maturity giving little margin for growth while digital has been the advertising channel with the biggest growth. Being FNG’s main business in the Pay- TV market, the company plans to invest in new Digital advertising solutions to keep ahead with the advertising landscape. An analysis of the advertising market comprising a primary and secondary research followed by a marketing and communications plan allowed to develop This is Fox as the solution for FNG to thrive in the online advertising market increasing by 1225% the online advertising revenue.